PARAMETER OSEANOGRAFI DI PERAIRAN NAMNGIL WOWO DESA WAB - Evangelin Martha Yulia Kadmaer; Anthon Daud Kilmanun (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2018)
This study was conducted on the moon April-May 2016 located in waters village the Wab Kabupaten Maluku Southeastern. The purpose of this research is to analyze parameter oceanography ( temperature, salinitas, current, pH, DO) in waters namngil wowo village the Wab. Data analyzed a sort of descriptive set by using microsoft excell in the charts. The result was found that in April, pH values highest station 8.16 on 1 and the lowest 7.84 on the station 3, value DO highest 5,27 in station 2 and the lowest 5.01 in station 1, value speed current highest 0.0565 m/det in station 2 and the lowest 0.0365 m/det in station 1, value temperature highest 31.05 oC in station 1 and the lowest 29.35 oC in station 5, the highest salinitas 35 o/oo in station 5 and the lowest 30.5 o/oo on the station 3. In may pH value highest station 8.16 on 2 and lowest 7.85 station at 4, Value do highest 4.93 in station 5 and the lowest 4.64 in station 1, value speed current highest 0.063 m/det in at station 4 and the lowest 0.049 m/det in station 5, value temperature highest 31.35 oC network in at station 4 and the lowest 30.25 oC network in station 3, The value of salinitas highest 35.5 o/oo on at station 4 and the lowest 34 o/oo station on 2.